2014
DOI: 10.1073/pnas.1405186111
|View full text |Cite
|
Sign up to set email alerts
|

RNA-directed gene editing specifically eradicates latent and prevents new HIV-1 infection

Abstract: Significance For more than three decades since the discovery of HIV-1, AIDS remains a major public health problem affecting greater than 35.3 million people worldwide. Current antiretroviral therapy has failed to eradicate HIV-1, partly due to the persistence of viral reservoirs. RNA-guided HIV-1 genome cleavage by the Cas9 technology has shown promising efficacy in disrupting the HIV-1 genome in latently infected cells, suppressing viral gene expression and replication, and immunizing uninfected cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
475
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 486 publications
(515 citation statements)
references
References 42 publications
(45 reference statements)
16
475
0
5
Order By: Relevance
“…In eukaryotes, the DSBs are more commonly repaired by the mechanism of error-prone non-homologous end joining (NHEJ), therefore generating sequence changes, for instance insertions and deletions (indels), around the DSBs . Owing to the simplicity of manipulation and versatility, the CRISPR/Cas9 system has been utilized as an attractive tool for various applications, such as genome-wide screening (Shalem et al, 2014;Zhou et al, 2014), gene repression and activation (Cheng et al, 2013;Doench et al, 2014;Gilbert et al, 2014), targeted fluorescence imaging (Tanenbaum et al, 2014) and novel approaches against pathogens including hepatitis B virus (Lin et al, 2014a;Seeger & Sohn, 2014), human papillomavirus (Kennedy et al, 2014), Epstein-Barr virus (Wang & Quake, 2014;Yuen et al, 2015), malaria (Wagner et al, 2014) and HIV-1 (Ebina et al, 2013;Hu et al, 2014;Ye et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In eukaryotes, the DSBs are more commonly repaired by the mechanism of error-prone non-homologous end joining (NHEJ), therefore generating sequence changes, for instance insertions and deletions (indels), around the DSBs . Owing to the simplicity of manipulation and versatility, the CRISPR/Cas9 system has been utilized as an attractive tool for various applications, such as genome-wide screening (Shalem et al, 2014;Zhou et al, 2014), gene repression and activation (Cheng et al, 2013;Doench et al, 2014;Gilbert et al, 2014), targeted fluorescence imaging (Tanenbaum et al, 2014) and novel approaches against pathogens including hepatitis B virus (Lin et al, 2014a;Seeger & Sohn, 2014), human papillomavirus (Kennedy et al, 2014), Epstein-Barr virus (Wang & Quake, 2014;Yuen et al, 2015), malaria (Wagner et al, 2014) and HIV-1 (Ebina et al, 2013;Hu et al, 2014;Ye et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Using a pair of sgRNAs targeting the LTR of HIV-1, it was shown that HIV-1 provirus can be removed from the genome of infected cell lines (Ebina et al, 2013;Hu et al, 2014). By combining TALEN or CRISPR/Cas9 with PiggyBac technology, researches have generated inducedpluripotent stem cells (iPSC) homozygous for the naturally occurring CCR5 D32 variant resistant to HIV-1 infection .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several research groups have successfully applied the type II CRISPR systemSpCas9 protein from Streptococcus pyogenes with guided RNA (gRNA)-for targeted genome editing in diverse cell types and organisms, including human cells [12][13][14] . Most recently, a couple of studies have demonstrated the excision of the HIV-1 provirus from the host cell genome using gene-editing tools [15][16][17][18] . Here we apply the CRISPR/Cas9 system to directly target and disrupt the reverse-transcribed products of the lentiviral RNA genome during their life cycle within host cells.…”
mentioning
confidence: 99%
“…This proviral targeting strategy was mimicked with both TALENs [132] against integrated lentiviral LTRs and CRISPR/Cas9 in single and multiple configuration [133]. The authors identified targets within the viral U3 LTR that resulted in excision of the entire 9709 bp proviral HIV DNA and prevented reinfection within latently infected T cells [133]. …”
Section: Applicationsmentioning
confidence: 99%